Experiment with air - Murphy, Bryan (Minneapolis, Minn. : Lerner Publications Co., 1991)
Presents simple experiments demonstrating the basic scientific principles of air.
"First published in 1991 by: Two-Can Publishing Ltd. ... London"--T.p. verso.
School Library Journal.
4.7.
4.7
3-6
Keywords: Air -- Experiments -- Juvenile literature; Air -- Experiments; Experiments; Air -- Experiments; Science -- Experiments